An Empirical Investigation of Exchange Rate Pass-Through in South Africa - Bhundia, Ashok (IMF Working Papers; Working Paper, 2002)
This paper analyzes the degree to which fluctuations in the nominal exchange rate passthrough to consumer prices in South Africa. While the average pass-through is found to be low, evidence from a structural vector autoregression suggests it is much higher for nominal (versus real) shocks. Historical decompositions suggest that the nominal exchange rate depreciation up to November 2001 is attributable primarily to negative real shocks, which explains why CPIX (consumer price index excluding interest on mortgate bonds) inflation did not increase significantly until December 2001, when positive nominal shocks began to contribute to the depreciation.